If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4=(x-9)-1/3
We move all terms to the left:
-4-((x-9)-1/3)=0
We multiply all the terms by the denominator
-((x-9)-1-4*3)=0
We calculate terms in parentheses: -((x-9)-1-4*3), so:We get rid of parentheses
(x-9)-1-4*3
We add all the numbers together, and all the variables
(x-9)-13
We get rid of parentheses
x-9-13
We add all the numbers together, and all the variables
x-22
Back to the equation:
-(x-22)
-x+22=0
We add all the numbers together, and all the variables
-1x+22=0
We move all terms containing x to the left, all other terms to the right
-x=-22
x=-22/-1
x=+22
| F(x)=76 | | 235+0.75d=125+1.63d; | | 5/2+p=p-8 | | (2x-7)/(x-6)=0 | | 6=k-3-8 | | -18+-9n+2n2+n3=0 | | 4x–2+3x+6= | | 3x-7+11(x-1)=15x-2 | | -1+12x=12x+17 | | b=463-61/3 | | 4x–2+3x+6=180 | | 7(16+y)+2y=13 | | 4(x-5)=-12+5x | | -7(-5g+20)=16+9g | | 16x-30=9x+23 | | 1/5x+200=300 | | y=416-9 | | 96-4.5y-3.2y=5.6y=42.80 | | -4+x=5x-4(1+3x) | | 69=4−2y−33y−69=4−2y−3 | | -(x/3)+10=18 | | 5(-2x+5)+6x=2(-2x-12-)-1 | | 4x^2+89=36x | | –9+3k=9+6k | | 2-8n=2 | | 17+4x=-13+6x | | b=10/2+251 | | -12x+37=51 | | 71+x+75=180 | | 5(a+4)+4=24 | | -6p+3p=-4-20 | | 5(-2x+5)+6x=2(-2x+12-12 |